Forward “MOMENTUM” in left ventricular assist systems: advanced engineering meets biology - Cleveland, Joseph C.; Goldstein, Daniel J.; Uriel, Nir; Mehra, Mandeep R.; MOMENTUM 3 Investigator, On behalf of the (Journal of Thoracic Disease, 2017)
The abandonment of need for pulsatile flow in favor of the unnatural physiology of continuous flow circulation with current left ventricular assist systems (LVAS) led to the widespread application of these devices in the patients with advanced heart failure refractory to medical therapy (1). Troublesome consequences, related to hemocompatibility related adverse effects (the clinical consequences of interaction between the device and blood interface) began to surface once long-term support was realized (2).